Association Between Telomere Length and Cardiovascular Risk: Pharmacological Treatments Affecting Telomeres and Telomerase Activity - Zafirovic, Sonja; Macvanin, Mirjana; Stanimirovic, Julijana; Obradovic, Milan; Radovanovic, Jelena; Melih, Irena; Isenovic, Esma (Current Vascular Pharmacology, 2022)
Telomeres represent the ends of chromosomes, and they are composed of an extensive number of – TTAGGG nucleotide sequence repeats in humans. Telomeres prevent chromosome degradation, participate in stabilization, and regulate the DNA repair system. Inflammation and oxidative stress have been identified as important processes causing cardiovascular disease and accelerating telomere shortening rate. This review investigates the link between telomere length and pathological vascular conditions from experimental and human studies. Also, we discuss pharmacological treatments affecting telomeres and telomerase activity.
Keywords: inflammation